Predicting lysine requirements using protein and lipid accretion curves for growing-finishing gilts - De La Llata, M.; Tokach, Michael D.; Goodband, Robert D.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A total of240 growing-finishing gilts (60 to 260 lb) was used to model accretion rates and the lysine:calorie ratio requirement based on lipid and protein growth. Real-time ultrasound measurements were used to estimate lipid and protein contents. These estimates then were translated into feed intake and lysine requirements. Gilts were fed one of eight different diet regimens, consisting of four increasing lysine:calorie ratios and two levels of fat (0 and 6%). Lipid and protein deposition rates could effectively model feed intake when pigs were fed lysine:calorie ratios close to their requirement. The modeled accretion rates effectively predicted the differences between treatments in agreement with the growth performance data. The modeled lysine:calorie ratio requirement accurately predicted the lysine:calorie ratios that maximized growth, evaluated by either the predicted or the actual data.
Keywords: Swine; Real-time ultrasound; Lipid accretion; Protein accretion; Lysine:calorie ratio; Fat; Lysine; Finishing pigs